Planning through exception: The rise of elite informality in Istanbul - Tomruk, Banu (Cities, 2026)
This article investigates how three large-scale mixed-use complexes in Istanbul (Zorlu Center, Mall of Istanbul, and Metropol Istanbul) consolidate a state-enabled mode of elite informality through discretionary plan revisions and regulatory flexibility. It analyzes document archives, site observations, and 30 semi-structured interviews conducted across the three sites to trace governance instruments, land conversions, and spatial outcomes. The cases share a monolithic, single-owner morphology with low perimeter permeability and consumption-oriented quasi-public realms. Ground-floor public open-space provision is conspicuously low (approximately 11 % at Zorlu, and about 5 % at Mall of Istanbul and Metropol), well below neighborhood-scale expectations derived from Istanbul's planning standards. Conceptually, the study situates these patterns within graduated sovereignty and planning-by-exception, showing how formal instruments are selectively mobilized to reallocate public or formerly public land for private returns. Building on these findings, the article advances auditable policy tools, minimum perimeter porosity and non-paywalled ratios in plan notes; ring-fenced value capture to deliver at-grade links and green areas; and a Social-Use Overlay to secure affordability when public/formerly public parcels are upzoned or disposed. The contribution is twofold: it reframes these projects as institutionalized, not anomalous, expressions of elite informality, and converts comparative insights into enforceable measures that align development rights with measurable civic returns. •Large mixed-use complexes entrench state-enabled elite informality.•Regulatory flexibility and opaque rezoning produce privatized urban enclaves.•Enclaved, low-porosity layouts privilege consumption over civic use.•Reforming urban governance requires transparency, participation, and legal accountability.•Auditable metrics and value capture can rebalance civic returns.